Laparoscopic versus Open Pediatric Surgery: Three Decades of Comparative Studies - Kiblawi, Rim; Zoeller, Christoph; Zanini, Andrea; Kuebler, Joachim F.; Dingemann, Carmen; Ure, Benno; Schukfeh, Nagoud (European Journal of Pediatric Surgery, 2021)
Introduction Despite its wide acceptance, the superiority of laparoscopic versus open pediatric surgery has remained controversial. There is still a call for well-founded evidence. We reviewed the literature on studies published in the last three decades and dealing with advantages and disadvantages of laparoscopy compared to open surgery.Materials and Methods Studies comparing laparoscopic versus open abdominal procedures in children were searched in PubMed/MEDLINE. Reports on upper and lower gastrointestinal as hepatobiliary surgery and on surgery of pancreas and spleen were included. Advantages and disadvantages of laparoscopic surgery were analyzed for different types of procedures. Complications were categorized using the Clavien–Dindo classification.Results A total of 239 studies dealing with 19 types of procedures and outcomes in 929,157 patients were analyzed. We identified 26 randomized controlled trials (10.8%) and 213 comparative studies (89.2%). The most frequently reported advantage of laparoscopy was shorter hospital stay in 60.4% of studies. Longer operative time was the most frequently reported disadvantage of laparoscopy in 52.7% of studies. Clavien–Dindo grade I to III complications (mild–moderate) were less frequently identified in laparoscopic compared to open procedures (80.3% of studies). Grade-IV complications (severe) were less frequently reported after laparoscopic versus open appendectomy for perforated appendicitis and more frequently after laparoscopic Kasai's portoenterostomy. We identified a decreased frequency of reporting on advantages after laparoscopy and increased reporting on disadvantages for all surgery types over the decades.Conclusion Laparoscopic compared with open pediatric surgery seems to be beneficial in most types of procedures. The number of randomized controlled trials (RCTs) remains limited. However, the number of reports on disadvantages increased during the past decades.
Keywords: minimally invasive surgical procedures; pediatrics; advantages; disadvantages; laparoscopy